(untitled) (Journal of Preventive and Social Medicine, 2024)
Background: Modern technology makes everything accessible and easy. In our daily life, we use lots of artificial intelligence. Our modern dentistry also uses lots of new technology. Methods: A total of 26 final-year BDS students of Marks Medical College (Dental Unit) were selected purposively and six respondents were selected among them by simple random sampling method for a focus group discussion session in June 2022. The study implemented one qualitative method: a focus group discussion (FGD) among respondents. Semi-structured interview guidelines study adhered to the consolidated reporting criteria for qualitative studies (COREQ) developed for the FGD. Results: Positive comments included the reduced workload, quick calculations, less radiation exposure, ease of choosing a treatment plan, and ease of motivating patients. On the negative side, it was noted that it was expensive, required additional funding for setup, wasn’t available, and required skilled labor to run, which is not readily available. Conclusion: It is encouraging that data-driven and robotic technology is becoming more prevalent in modern dentistry. AI and related advancements are becoming more common and used in healthcare. Dental surgeons should be more knowledgeable to use this technology. JOPSOM 2021; 41(2):57-61